Morphological, Biochemical, and Molecular Diversity Assessment of Egyptian Bottle Gourd Cultivars - Ehab A. Ibrahim; Haifa A. S. Alhaithloul; Sahar A. M. Shamseldin; Sara B. H. Awaly; Abd El-Latif Hesham; Mohamed F. M. Abdelkader; Mesfer M. Alqahtani; Fahad Mohammed Alzuaibr; Abdulrahman Alasmari; Noha A. Sukar; Mohamed Z. Diyasty; Mohamed A. Abdein (Genetics Research)
The genetic variability and relationships between ten bottle gourd cultivars were evaluated based on morphological, biochemical, and molecular parameters. The results displayed high variability among selected cultivars in terms of photosynthetic pigments, total free amino acids, total phenol content, isozymes pattern, and protein electrophoresis. Furthermore, differences in molecular markers were revealed by the SCoT technique. The peroxidase (POD) and polyphenyl oxidase (PPO) isozymes patterns did not detect significant differences in bands among cultivars. The protein patterns revealed seventeen bands ranging from 126 to 9 kDa and five polymorphic bands representing 29.41%. On the other hand, eight SCoT primers were used to evaluate the genetic variability and relationships between the ten Egyptian bottle gourd cultivars. The results of SCoT analysis detected 44 amplicons with 50% polymorphism. In addition, the results of the phylogenetic tree that is constructed based on the similarity coefficient revealed by SCoT analysis confirm the results of biochemical analysis indicating a genetic relationship between the most efficient bottle gourd cultivars (S1 and S2 cultivars). In addition, there is a genetic relationship among the less efficient bottle gourd cultivars (S4 and S5 cultivars). These results could be beneficial to distinguish among bottle gourd cultivars in the plant breeding programs.